Existence principles for second order nonresonant boundary value problems. (1994) - O'Regan, Donal
Abstract : We discuss the two point singular nonresonant boundary value problem 1 p ( p y ′ ) ′ = f ( t, y, p y ′ ) a.e. on [ 0, 1 ] with y satisfying Sturm Liouville, Neumann, Periodic or Bohr boundary conditions. Here f is an L 1 -Carathéodory function and p ∈ C [ 0, 1 ] ∩ C 1 ( 0, 1 ) with p > 0 on ( 0, 1 ) .